Conceptual science and beyond : general chemistry 2 : a worktext for senior high school - Rodil, Mary Sheenalyn P.; Cuarto, Ceazar Ryan U. (Quezon City : Brilliant Creations Publishing, Inc., 2018)
"This book has been published to serve the needs of the Senior High School students who will be taking up General Chemistry under the STEM Strand. To enhance students understanding of the fundamentals of Chemistry, interactive activities, laboratory experiments, computational problems, and other manipulative and research activities have been included in this textbook."
Includes bibliographical references.
English text.
Keywords: Chemistry